2020
DOI: 10.1016/j.physletb.2020.135416
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of RN-AdS fluids

Abstract: We establish the parameter space geometry of a fluid system characterized by two constants, whose equation of state mimics that of the RN-AdS black hole. We call this the RN-AdS fluid. We study the scalar curvature on the parameter space of this system, and show its equivalence with the RN-AdS black hole, in the limit of vanishing specific heat at constant volume. Further, an analytical construction of the Widom line is established. We also numerically study the behavior of geodesics on the parameter space of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A similar situation occurs with Θ, as we explain via equation (10). Importantly, for relations E and F to be physically justifiable, R should have dimensions of volume, due to which thermodynamic geometry is always defined via potentials per unit volume (for a more detailed discussion in the context of black holes, see [14,15]). Keeping these issues in mind, in this paper we shall introduce a new metric on the parameter manifold which is conformally related to the known FIM, but in which R is invariant under the CT and so is Θ, so that properties A-D are retained.…”
Section: Introductionmentioning
confidence: 79%
“…A similar situation occurs with Θ, as we explain via equation (10). Importantly, for relations E and F to be physically justifiable, R should have dimensions of volume, due to which thermodynamic geometry is always defined via potentials per unit volume (for a more detailed discussion in the context of black holes, see [14,15]). Keeping these issues in mind, in this paper we shall introduce a new metric on the parameter manifold which is conformally related to the known FIM, but in which R is invariant under the CT and so is Θ, so that properties A-D are retained.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, we shall be exploring a fluid-like description of black hole microstructures which may be thought of as being analogous to the molecules present in a fluid. Since v 2r + corresponds to the specific (fluid) volume of the black hole, a number density ρ 1/v can be naturally associated with the system [80,86,87]. One can then alternatively write the equation of state [Eq.…”
Section: Microstructures Of Black Holes and A Mean Field Descriptionmentioning
confidence: 99%
“…where Q i and J k are the charge parameter and the angular momentum parameter, respectively. Based on this issue, a series of studies on the thermodynamic behavior of AdS black holes have been done in the extended phase space [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Firstly, people found that the charged AdS black hole has a behavior similar to Van de Waals phase transition when choosing the quantities P and V as the independent dual variables.…”
Section: Introductionmentioning
confidence: 99%